Stress and Coping Among Orthopaedic Surgery Residents and Faculty - Sargent, M. Catherine; Sotile, Wayne; Sotile, Mary O.; Rubash, Harry; Barrack, Robert L. (Journal of bone and joint surgery. American volume, 2004)
BackgroundEvaluations of physicians and residents have revealed concerning levels of psychosocial dysfunction. The purposes of this study were to determine the quality of life of orthopaedic residents and faculty and to identify the risk factors for decompensation.MethodsTwenty-one orthopaedic residents and twenty-five full-time orthopaedic faculty completed a 102-question voluntary, anonymous survey. The survey consisted of three validated instruments, i.e., the Maslach Burnout Inventory, the General Health Questionnaire-12, and the Revised Dyadic Adjustment Scale; and three novel question sets addressing background and demographic information, stress reaction and management, and the balance between work and home life. Descriptive statistics, pairwise correlations, simple t tests, and Pearson and nonparametric Spearman correlations were calculated. The simple correlation coefficient was used to assess bivariate relationships.ResultsThe mean overall quality-of-life score, on a scale of 0 to 4 points, was 2.5 points for residents compared with 3.6 points for faculty members. Residents reported considerable burnout, showing a high level of emotional exhaustion and depersonalization and an average level of personal achievement, whereas faculty reported minimal burnout, showing a low level of emotional exhaustion (p < 0.0003), an average level of depersonalization (p < 0.0001), and a high level of personal achievement (p < 0.0001). Only two of twenty-five faculty members (compared with seven of twenty-one residents) scored over 4 points on the General Health Questionnaire-12, indicating significant symptomatology (p < 0.01). The majority of subjects reported that a partner or spouse showed nondistressed levels of marital adjustment and satisfaction. All residents and nine of the twenty-five faculty members had mentors but judged the resource to be minimally beneficial. Resident burnout and psychiatric morbidity correlated with weekly work hours; conflict between the commitments of work and home life; discord with faculty, nursing staff, and senior residents; debt load; and work-related stress. Protective factors included being a parent, spending time with a spouse, having a physician father, and deriving satisfaction from discussing concerns with colleagues, friends, and family.ConclusionsIn pursuit of our goal of determining the quality of life of orthopaedic residents and faculty, we identified a large disparity between the two groups. The resident group reported much greater levels of dysfunction particularly with regard to burnout and psychiatric morbidity. Furthermore, with regard to our second goal; our data revealed a number of risk factors for resident decompensation, most notably, increased workload, high debt levels, and discord with superiors. In addition, our research revealed that the current support interventions by the residency program, including mentoring and facilitation of spousal adjustment, are viewed as being of little help.